Increasing fatigue durability of a bolt joint/Srieginės jungties ciklinio ilgaamžiškumo didinimas taikant detalių tarpusavio pasukimių būdą - Krenevičius, Algimantas; Vislavičius, Kęstutis (Journal of Civil Engineering and Management, 2000)
A method of increasing the fatigue durability of a bolt joint is considered. It is based on the position of the nut with respect to the bolt. Turning the nut causes its threads to be in contact with different threads of the bolt during sequential periods of use. The thread of the bolt which experiences the highest loading is in contact with the first (most dangerous) thread of the nut. With further nut turns, the bolt thread experiences less loading because of the contact with another (less dangerous) threads of the nut. Reducing the loading in this way can increase the fatigue durability. The nut position with respect to the bolt can be controlled using different heights of washer-bushing. The durability calculation is based on the fatigue curve for the bolt joint when it is tested without turning the nut. The sum of damage is calculated for all points of the bolt thread which are in contact with the first turn of the nut for any loading period. According to the Miner's rule, fatigue failure occurs when the sum of damage is equal to one. The mathematical model for calculating the maximum fatigue durability of bolt joint is given. It is assumed that the height of washer-bushing, the number of turns of the nut and the fatigue curve for the threaded bolt joint are known. The survival condition is that for any point on the bolt, the sum of damage after the last loading period must be less than one. A personal computer program for the fatigue durability calculation is prepared, and some example problems are solved. An analysis of the results is presented.Article in Lithuanian.First Published Online: 26 Jul 2012